PERFORMANCE OF ARABIC EDUCATION LECTURERS IN DEVOTION OF LANGUAGE LEARNING - Qodri, Muhammad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
This article aims to find out how the performance of lecturers in designing, implementing and evaluating learning language proficiency courses. This article uses a descriptive qualitative approach. data collection through interviews, observation, and documentation. Data collected using snowball sampling techniques and data collected were analyzed through the steps of data reduction, data presentation, and drawing conclusions. The findings of this article are: performance of Arabic education lecturers faculty of Tarbiyah in devotion of language learning that lecturer has not maximized the potential in giving lectures, coupled with the preparation of SAP courses that are lacking  this is seen in 1) the design of learning made by lecturers listening and reading in the form of SAP, only briefly explains about several components, namely the identity of the course, learning outcome indicators,  lecture method, assessment, and bibliography, mentions several reading sources used in the listening learning process and reading, 2) the implementation of learning include: preliminary activities, core activities, and closing activities, 3) the evaluation of learning outcomes is an activity of measuring the level of success and ability of students in the learning process.